Thrombolytic Activity and Preliminary Cytotoxicity of Five Different Fractions of Methanol Extract of Allamanda cathartica Leaf - Rehan Sarker, Tasnuva Sharmin, Sharmin Reza Chowdhury, Farhana Islam (Journal of Applied Pharmaceutical Science)
Investigation with the crude methanol extract of Allamanda cathartica leaves and its different fractions were carried out to evaluate its possible thrombolysis and cytotoxic activities. A quick & rapid methodology (In-vitro Thrombolytic model) was applied to find out their thrombolytic potential where streptokinase and water were employed as a positive and negative controls, respectively. Among the extractives, the chloroform (CSF) and hexane (HSF) soluble fractions showed 34.51±0.669% and 32.179±0.581% clot lysis activity respectively compared to standard streptokinase which exhibited 61.5% lysis of clot. In brine shrimp lethality bioassay method, the LC50 values of the test samples of A. cathartica leaves were assayed where DMSO and Vincristine sulphate were used as solvent & as positive control respectively. The chloroform, hexane and carbon tetrachloride soluble fractions showed significant cytotoxic activity against brine shrimp nauplii and LC50 values were 1.45, 5.00 and 5.24 μg/ml respectively.
Keywords: Allamanda cathartica,Clot lysis,In-vitro Thrombolytic model,Streptokinase,Cytotoxic activity.